2007
DOI: 10.1111/j.1467-6494.2007.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Passion in Performance

Abstract: The present paper reports two studies designed to test the Dualistic Model of Passion with regard to performance attainment in two fields of expertise. Results from both studies supported the Passion Model. Harmonious passion was shown to be a positive source of activity investment in that it directly predicted deliberate practice (Study 1) and positively predicted mastery goals which in turn positively predicted deliberate practice (Study 2). In turn, deliberate practice had a direct positive impact on perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
428
3
25

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(527 citation statements)
references
References 40 publications
37
428
3
25
Order By: Relevance
“…In contrast, the present study found a positive correlation, as have previous studies with students (e.g., Vallerand et al, 2008;Vallerand et al, 2007). Students high in obsessive passion also tended to be high in harmonious passion which-as the regression analyses controlling for the overlap between the two forms of passion indicated-may explain the negative correlation between obsessive passion and cynicism (cf.…”
Section: Discussionsupporting
(Expert classified)
See 1 more Smart Citation
“…In contrast, the present study found a positive correlation, as have previous studies with students (e.g., Vallerand et al, 2008;Vallerand et al, 2007). Students high in obsessive passion also tended to be high in harmonious passion which-as the regression analyses controlling for the overlap between the two forms of passion indicated-may explain the negative correlation between obsessive passion and cynicism (cf.…”
Section: Discussionsupporting
(Expert classified)
“…In obsessive passion, individuals engage in an activity because of intra-or interpersonal pressure, and engaging in the activity diverts time and resources away from other life domains. Here, the passion controls the person (Vallerand, 2008;Vallerand et al, 2003Vallerand et al, , 2007.…”
Section: Passion and Motivation For Studying: Predicting Academic Engmentioning
confidence: 99%
“…Harmonious passion is caused by the free acceptance of an activity which is in harmony with other aspects of the person's life. Obsessive passion is an uncontrollable urge to engage in the activity with a rigid persistence that creates intra-and interpersonal conflicts (Vallerand & Verner-Filion, 2013;Vallerand et al, 2007). Harmonious passion contributes to raising the game performance and enjoyment of the game (Przybylski, Weinstein, Ryan, & Rigby, 2009) while obsessive passion favors a disordered pattern of play, more tension after playing and less enjoyment, along with negative affect (Lafreni ere, Vallerand, Donahue, & Lavigne, 2009), and the difficulty to regulate time spent playing (Fuster, Chamarro, Carbonell, & Vallerand, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vallerand et al (2003) designed the Dual Model of Passion, defining passion as a strong inclination toward an activity that is liked, is important to the individual and in which time is invested. The model identifies two types of passion -harmonious and obsessive -each associated with different outcomes and experiences (Vallerand et al, 2003(Vallerand et al, , 2007. Harmonious passion is caused by the free acceptance of an activity which is in harmony with other aspects of the person's life.…”
Section: Introductionmentioning
confidence: 99%
“…Passion has been also linked with students' persistence (BonnevilleRoussy et al, 2013), the daily or weekly time they spent to the passionate activity (Bonneville-Roussy et al, 2011; Stoeber et al, 2011; Vallerand et al, 2007), and the students' academic engagement (Stoeber et al, 2011). It would be interesting to note that if a student persists on a task, spend a lot of time, and is committed to it, it is not uncommon to expect that it could also benefit his/her academic performance.…”
Section: Why Passion Is Important In Educationmentioning
confidence: 99%